MORFOTEKTONIK DAN POTENSI BENCANA ALAM DI LEMBAH KERINCI SUMATERA BARAT, BERDASARKAN ANALISIS POTRET UDARA - S. Poedjopradjitno (Pusat Survei Geologi, 2012)
An interpretation of 1971 aerial photograph (phanchromatic) of the Kerinci valley area is intended to identify morphotectonic elements, in order to examine the genesis of Kerinci valley and to delineate a potential natural disasters zone. The interpretation shows the trace of macro morphotectonic elements related to the tectonic movements in the past, such as old faultscarp, young faultscarp, small faultscarp, shifting river channel, alignment of the valley and lineaments. Therefore landscape of the Kerinci valley was produced by structure activities that are dominated by vertical movements. Besides some of tectonic movements accompanying landforms are observed, such as a pile of fluvio volcanic fan and terrace deposites. The faultscarp pattern extends parallel to the direction of main fault in the Sumatra island and become narrows at the northern end. In this area is very potential for earthquakeKey words : morfotectonic, faultscarp, alignment, alluvial fan, earthquake